Freud? Non è mai esistito. Riflessioni su una sentenza della Corte di Cassazione - Anzilotti, Carlo; Brandizzi, Martina (Il sogno della farfalla, 2018)
A ruling of the Italian Supreme Court in April 2011 defines psychotherapy as a typical act performed by the medical profession given that it is a therapy whose ultimate aim is to cure a patient of real and proper illnesses. Thereby debunking the idea that the profession of psychoanalyst is different from that of the psychotherapist. Taking the ruling as its starting point the article then traces the history of psychoanalysis and its relationship with psychiatry and psychotherapy. The article highlights the attempts made, present from the very start, to discredit psychotherapy and relegate it to the role of providing support to those unable to turn to psychoanalysis either as a result of limited economic means or because suffering from serious psychic pathologies. The Supreme Court restores a specific medical identity to psychotherapy and prompts a further look at those theories and practices that go by the name of psychotherapy despite not having the aim to cure.